2003
DOI: 10.1046/j.1432-1033.2003.03792.x
|View full text |Cite
|
Sign up to set email alerts
|

A pathway through interferon‐γ is the main pathway for induction of nitric oxide upon stimulation with bacterial lipopolysaccharide in mouse peritoneal cells

Abstract: Production of nitric oxide (NO) in response to bacterial lipopolysaccharide (LPS) was investigated using cultures of mouse peritoneal exudate cells (PEC) and the macrophage cell line RAW264.7. In the presence of anti-(interferon-c) (IFN-c), NO production was markedly suppressed in the PEC culture but not in the RAW264.7 culture. In the PEC culture, LPS induced both IFN-c production and activation of IFN response factor-1, which leads to the gene expression of inducible NO synthase, but neither was induced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
1
29
0
2
Order By: Relevance
“…In a previous paper (22), we demonstrated that mouse RAW264.7 cells did not produce IL-12 in response to LPS while they responded normally in inducing several cytokines other than IL-12. The impaired responses of RAW264.7 cells to LPS-induced IL-12 production were investigated in this study to elucidate the regulatory mechanisms.…”
mentioning
confidence: 78%
“…In a previous paper (22), we demonstrated that mouse RAW264.7 cells did not produce IL-12 in response to LPS while they responded normally in inducing several cytokines other than IL-12. The impaired responses of RAW264.7 cells to LPS-induced IL-12 production were investigated in this study to elucidate the regulatory mechanisms.…”
mentioning
confidence: 78%
“…[35,39,40]. Previous studies suggested that NO is produced via the induction of iNOS by macrophages in response to outside stimuli [41].…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor (PPAR) ␥ , a nuclear receptor with anti-infl ammatory functions, is barely detectable in RAW264.7 cells ( 12,13 ), but it is highly expressed in TGEM cells ( 13 ). IL-12p70 and interferon (IFN)-␥ are not produced by RAW264.7 cells upon LPS stimulation ( 14 ). Caveolin-1 (Cav1), which is essential for the assembly of caveolae and involved in the maintenance of cellular cholesterol homeostasis and lipid transport ( 15 ), is upregulated in peritoneal macrophages in response to LPS but downregulated in RAW264.7 cells ( 16,17 ).…”
Section: Use Of Pearson Correlation and A Distance-based Correlation mentioning
confidence: 99%